Соціальна політика України щодо ветеранів війни: перспективи реінтеграції в цивільне життя - Загоруй, І. С.; Загоруй, Л. М. (НДІ ПЗІР НАПрН України, 2024)
Засадничі основи конституційного ладу України, визнані й закріплені конституційні права людини та громадянина в Україні дають підставу стверджувати, що соціальна державна політика є пріоритетною, орієнтованою на реалізацію соціальних прав і потреб людини, громадян та соціальних груп. Поняття соціальної політики здебільшого пов’язується із системою державних заходів щодо регулювання відносин між соціальними групами з метою підвищення суспільного добробуту, поліпшення якості і рівня життя, раціонального використання трудових ресурсів тощо. Серед загальних питань соціальної політики в Україні актуалізується сфера соціальної ветеранської політики, пов’язаної з соціальною реінтеграцією ветеранів війни. The fundamental principles of Ukraine's constitutional order, recognized and enshrined human and civil rights in Ukraine, provide grounds to assert that social state policy is a priority, aimed at the realization of social rights and needs of individuals, citizens, and social groups. The concept of social policy is mostly associated with a system of state measures to regulate relations between social groups to improve public welfare, enhance the quality and standard of living, and ensure the rational use of labor resources, among other objectives. Among the general issues of social policy in Ukraine, the sphere of social veteran policy, related to the social reintegration of war veterans, is becoming more relevant.
Keywords: соціальна політика; соціальний захист; послуга; пільга; ветерани війни; соціальна реінтеграція; social policy; social protection; service; benefit; war veterans; social reintegration